A CONCEPT OF AMA IN AYURVEDIC SYSTEM OF MEDICINE - AN OVERVIEW - Babnrao Chavan, *Avinash; K. Jadhav, Dnyaneshwar (International Journal of Ayurveda and Pharma Research, 2017)
Ayurved have its own concepts like Dosh, Dushay, Mala, Agni etc. Aam is one of the concepts which take major role to produce variety of disease. Aam is unripe, undigested food which cause due to Agnimandhy. Aam production cause Agnimandhy & vice versa. We all know that all disease occurs due to Agnimandhy only. If Agni get destroy then human get die. Aam is root cause of all disease. Now days, due to increasing pollution, incapability to obey the rules of sound body maintence and lack of exercise and notorious diet, the immunity being is decreased. Because of this variety of disease produced. Ama production can result in variety of diseases like Amvata (Rheumatoid arthritis), Sandhigata-vata (osteoarthritis), Katigat-vata (low-back pain), Tamaksvasa (Asthma), and Pakvasjayagata. The concept of Ama is the most important fundamental principle of Ayurveda in understanding the physio-pathology of the diseases. Aamvichar have own importance in Nidan & Chikitsa of disease. The choice of kalpa changes according to Sama and Niram avashta. Ayurveda attributes cause of any disease to an imbalance in one or all of the Dosh and for successful treatment of a particular disease Vaidya has to determine, weather the imbalanced Dosh is Saam or Niram. If Vaidya can understand this stage well and give its drug as per Avashta then it will be give miraculous result. In this review article cover all points related to Aam from samhita & available latest literature from internet.